A Systematic Review Comparing the Surgical Outcomes of Open Versus Minimally Invasive Surgery for Congenital Diaphragmatic Hernia Repair - Quigley, Conall P; Folaranmi, Semiu E (Journal of laparoendoscopic & advanced surgical techniques. Part A, 2023)
Surgical intervention is the definitive management for congenital diaphragmatic hernia (CDH) repair from 1902. Since this time, two mainstay approaches have been used, open and minimally invasive surgical (MIS) repair. An invasive laparotomy is used in around 91% of cases. So, this systematic review of the published literature will compare the surgical outcomes of open (CDH) repair vs MIS for CDH repair and will determine which approach is superior. Our literature search across MEDLINE and EMBASE included articles from 2004 to 2022, incorporating pediatric CDH repairs, human subjects only, and English language articles. Primary outcomes analyzed were rate of recurrence, length of surgery, length of hospital stay, use of diaphragmatic patch, mortality, postoperative chylothorax, and extracorporeal membrane oxygenation (ECMO) use postoperatively. After application of exclusion criteria, 32 articles were reviewed. Comparison of MIS repair versus open repair had a rate of recurrence at 8.6% versus 1.6% ( < .00001). Length of hospital stay was 19.6 days versus 33.6 days ( = .0012), mortality rate at 4.6% versus 16.6% ( < .0001), patch repair required in 19.6% versus 55.4% ( = < .00001), and postoperative ECMO use of 3.7% versus 12.3% ( < .00001), respectively. MIS repair is associated with decreased length of hospital stay, reduced mortality rate, and postoperative ECMO usage. Hernia recurrence is still high among MIS repair groups compared to the open repair groups. Large, multicentered randomized control trials are recommended for further analysis to decipher the true superior surgical intervention.